Nursing Students’ Experiences of Basic Life Support Training and Its Role in Emergency Care Competence - N Adi Sumartawan; Grzegorz Wróbel; Florjana Rustemi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study explored how BLS training shapes emergency care competence development and early professional identity among vocational nursing students. Methodology: A qualitative descriptive design with thematic analysis was employed. Data were collected through semi-structured interviews with vocational nursing students following structured BLS simulation training. Data were analysed using NVivo to generate hierarchical coding structures and thematic integration. Main Findings: Four interrelated themes emerged: (1) transformative experiential learning through embodied simulation, repetition, and instructor feedback; (2) multidimensional construction of emergency competence characterised by confidence, situational awareness, and readiness to act; (3) emotional and contextual barriers including performance anxiety and fear of clinical error; and (4) emerging professional identity grounded in ethical responsibility and teamwork. Competence development was constructed not merely as technical mastery but as embodied readiness moderated by emotional regulation and supported by structured experiential exposure.. Novelty/Originality of this study: BLS training functions not only as a technical instructional strategy but as a formative process shaping cognitive preparedness, emotional regulation, and early professional identity. Integrating structured simulation, reflective debriefing, and role clarification into vocational nursing curricula may enhance emergency care competence development.